Characterization of the feedstock properties of metal injection-molded WC-Co with palm stearin binder system - Sri Yulis M. Amin,; Norhamidi Muhamad,; Khairur Rijal Jamaludin,; Abdolali Fayyaz,; Heng, Shye Yunn (Universiti Kebangsaan Malaysia, 2014)
Feedstock preparation, as well as its characterization, is crucial in the production of highly sintered parts with minimal defect. The hard metal powder - particularly, cemented carbide (WC-Co) used in this study was investigated both physically and thermally to determine its properties before the mixing and injection molding stage. Several analyses were conducted, such as scanning electron microscopy, energy dispersive X-ray diffraction, pycnometer density, critical powder volume percentage (CPVP), as well as thermal tests, such as thermogravimetric analysis and differential scanning calorimetry. On the basis of the CPVP value, the feedstock, consisting of WC-Co powder, was mixed with 60% palm stearin and 40% polyethylene at an optimal powder loading, within 2 to 5% lower than the CPVP value. The CPVP spotted value was 65%. The feedstock optimal value at 61% showed good rheological properties (pseudoplastic behavior) with an n value lower than 1, considerably low activation energy and high moldability index. These preliminary properties of the feedstock serve as a benchmark in designing the schedule for the next whole steps (i.e. injection, debinding and sintering processes).